Improving the legislation of the Republic of Kazakhstan in the field of prevention of domestic violence: current problems and solutions - Kambarov, A.K.; Muratkhanova, M.B.; Ashimova, E.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The article examines the national legislation of the Republic of Kazakhstan regulating the prevention of domestic violence. An analysis of its content and application practices has been carried out, key implementation problems have been identified, and possible modernization directions have been outlined. The relevance of the study is related to the growing number of reported cases of domestic violence, as well as the need to implement strategic government documents, including the Concept of Family and Gender Policy until 2030. The special Law «On the Prevention of Domestic Violence» in force in Kazakhstan has revealed a number of shortcomings in practice: low effectiveness of interdepartmental cooperation, limited preventive measures with offenders, incomplete registration of perpetrators of violence, as well as difficulties in identifying violence against women and children. The article also compares the experience of the Kyrgyz Republic, where recent legislative changes have increased responsibility for such offenses. Based on scientific research and practical recommendations, measures are proposed to improve Kazakhstan's legislation: strengthening the coordination of government agencies, introducing effective algorithms for early detection and response, developing a victim support system, as well as increasing the effectiveness of preventive measures against aggressors.